Experimental Study on Methane Desorption from Lumpy Coal under the Action of Hydraulic and Thermal. (30th April 2018) - Zhao, Dong; Li, Dayuan; Ma, Yulin; Feng, Zengchao; Zhao, Yangsheng
Abstract : Moisture and thermal are the key factors for influencing methane desorption during CBM exploitation. Using high-pressure water injection technology into coalbed, new fractures and pathways are formed to transport methane. A phenomenon of water-inhibiting gas flow existed. This study is focused on various water pressures impacted on gas-adsorbed coal samples, and then the desorption capacity could be revealed under different conditions. And the results are shown that methane desorption capacity was decreased with the increase in water pressure at room temperature and the downtrend would be steady until water pressure was large enough. Heating could promote gas desorption capacity effectively, with the increasing of water injection pressures, and the promotion of thermal on desorption became more obvious. These results are expected to provide a clearer understanding of theoretical efficiency of heat water or steam injection into coalbed, and they can provide some theoretical and experimental guidance on CBM production and methane control.